Self-Evolvable Systems Machine Learning in Social Media - Iordache, Octavian (Springer eBooks, 2012)
This monograph presents key method to successfully manage the growing  complexity of systems  where conventional engineering and scientific methodologies and technologies based on learning and adaptability come to their limits and new ways are nowadays required. The transition from adaptable to evolvable and finally to self-evolvable systems is highlighted, self-properties such as self-organization, self-configuration, and self-repairing are introduced and challenges and limitations of the self-evolvable engineering systems are evaluated.